2019
DOI: 10.1183/13993003.00655-2019
|View full text |Cite
|
Sign up to set email alerts
|

The global prevalence of latent tuberculosis: a systematic review and meta-analysis

Abstract: In 1999, the World Health Organization (WHO) estimated that one-third of the world's population had latent tuberculosis infection (LTBI), which was recently updated to one-fourth. However, this is still based on controversial assumptions in combination with tuberculin skin test (TST) surveys. Interferon-γ release assays (IGRAs) with a higher specificity than TST have since been widely implemented, but never used to estimate the global LTBI prevalence.We conducted a systematic review and meta-analysis of LTBI e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
264
4
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 377 publications
(292 citation statements)
references
References 105 publications
(81 reference statements)
8
264
4
16
Order By: Relevance
“…The analysis combining TST and IGRAs found a prevalence of LTBI of 25.2% (IGRAs-based prevalence) and 27.1% (>10 mm TST-based prevalence). Therefore, COHEN et al [24] in this study found global LTBI prevalence similar to that reported by HOUBEN and DODD [19] in 2016, with an estimate of 23%, but lower compared with that 32% estimated by WHO in 1999. The higher LTBI prevalence estimated by WHO can be attributed to the epidemiology of 1999, when TB incidence was higher with consequently higher M. tuberculosis transmission rates.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The analysis combining TST and IGRAs found a prevalence of LTBI of 25.2% (IGRAs-based prevalence) and 27.1% (>10 mm TST-based prevalence). Therefore, COHEN et al [24] in this study found global LTBI prevalence similar to that reported by HOUBEN and DODD [19] in 2016, with an estimate of 23%, but lower compared with that 32% estimated by WHO in 1999. The higher LTBI prevalence estimated by WHO can be attributed to the epidemiology of 1999, when TB incidence was higher with consequently higher M. tuberculosis transmission rates.…”
supporting
confidence: 83%
“…The manuscript of COHEN et al [24], entitled "The global prevalence of latent tuberculosis: a systematic review and meta-analysis", published in this issue of the European Respiratory Journal, describes LTBI prevalence worldwide. Different from previous studies that used mathematical models, they systematically collated the current evidence published in scientific journals and provided quantitative estimates with a meta-analysis approach.…”
mentioning
confidence: 99%
“…En un metaanálisis que estimó la prevalencia global de ITLB a partir de 88 estudios de 36 países, publicados entre 2005 a 2018 (Cohen et al) 21 , la prevalencia de ITBL con prueba de interferón gamma fue de 24.8 % (IC95 % 19.7-29.9 %) y con PPD fue de 21.2 % (IC95 % 17.9-24.2 %). Al comparar estos resultados con lo encontrado en esta revisión, se observó que del total de publicaciones nueve de ellas reportaron prevalencias mayores a la estimada en esa revisión sistemática, cuatro publicaciones tenían prevalencias similares y solamente una de ellas tenía una prevalencia menor.…”
Section: Discussionunclassified
“…Al realizar la comparación entre las dos revisiones sistemáticas, se observó que la carga de ITBL sigue siendo mayor en personal de salud en comparación con la población general, ya que la revisión sistemática y metaanálisis de la prevalencia de ITBL en trabajadores de salud de países con más carga por TB, obtuvo una prevalencia global de 47 % (IC95 % 34-60) y en Brasil de 37 % (IC95 % 17-56), siendo mucho mayor de lo reportado por Cohen 21 .…”
Section: Discussionunclassified
“…Latent tuberculosis infection (LTBI) is defined by the World Health Organization (WHO) as "a state of persistent immune response to stimulation by Mycobacterium tuberculosis antigens without evidence of clinically manifested active TB" (WHO, 2019). An estimated 1.8 billion people worldwide have LTBI, with wide variations in LTBI rates across countries (Houben and Dodd, 2016;Knight et al, 2019;Huaman and Sterling, 2019;Cohen et al, 2019). LTBI can be due to infection with either drug-sensitive or drugresistant M. tuberculosis (Mtb) strains.…”
Section: Introductionmentioning
confidence: 99%